New York State Association of Wholesale Marketers & Distributors Annual Meeting Journal - SICILIANO A; ALTMAN S; BUTTON M; FINKLE D; NAIGLES E (Tufts Archival Research Center, 2007)
Marginalia; Journal of 1997 New York State Association of Wholesale Marketers and Distributors annual meeting. Contains events schedule, 1997 honorees, names of convention guests and donors. Lists accomplishments of NYSAWMD in past year, especially pertaining to tobacco legislation. Includes articles discouraging tobacco regulation and extensive graphs and tables of cigarette tax rates.